SiNPs Porous Microspheres Promote Proliferation and Differentiation of hDPSCs - Clin Prof Yihong Liu; Dr BingQing Li; Dr JingRen Zhao (Elsevier, 2023)
Aim or Purpose: SiNPs porous microspheres were fabricated and characterized. Their effect on proliferation and differentiation of hDPCs were studied in vitro. Materials and Methods: PLGA/SiNPs or PLGA porous microspheres were fabricated with modified double emulsion solvent evaporation methods. The hDPCs were inoculated with the bio-scaffolds. The PLGA group was consisted as positive controls. The morphology of microspheres was investigated by SEM. Elemental composition and dispersion were characterized by EDX. The surface area was analyzed by BET test. The cell biocompatibility was studied by confocal laser-scanning microscopy and CCK-8 assay. The osteogenic and odontogenic properties were detected by ALP activity quantification, alizarin red staining and immunofluorescence staining for OCN and DSPP. Results: 1) The microspheres were superficially porous and coarse with similar inter-connected pores inside. 2) SiNPs were mainly encapsulated inside the microspheres. 3) Surface area of the PLGA/SiNPs group was significantly larger than the PLGA group(P<0.05). 4) CCK-8 assay results demonstrated there was no significant difference in the cell proliferation viability of the two groups at 1, 3, 5, 7, days (P > 0.05), while PLGA/SiNPs sustained the promotion ability until 11days. 5) The alkaline phosphatase staining showed stronger results in group PLGA/SiNPs after 7 days. 6) The ALP activity in the two groups continuously increased over time, reaching the peak on the 14th day, and then declined on the 21st day. There was no significant difference in the two groups (P>0.05). 7) After osteoinduction for 28 days DSPP expression were uniquely detected in PLGA/SiNPs group. Conclusions: SiNPs could promote the proliferation and osteogenic/odontogenic differentiation of hDPCs.